Conformity of Goods and Guarantee in Hungarian Law : Example of Transposition of Directive 1999/44/EC by Amending the General Rules of Contract Law - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
In 2002 Hungary transposed the Directive 1999/44/EC on certain aspects of sale of consumer goods and associated guarantees, by amending the Civil code of 1959, rather than integrating the rules of the Directive into the then-effective Law on the Protection of Consumers of 1997. Such an approach reveals some advantages if compared to the Serbian law. Namely, in Serbia the former Law on the Protection of Consumers of 2010 introduced special rules pertaining to conformity and guarantees in consumer sales contracts. Consequently, the need arose to limit their scope of application from the general rules of the Law on Obligations of 1978 on the conformity and guarantees. By the transposition of the rules of Directive into the Hungarian Civil code a unique set of rules on conformity and guarantees has been created that has a general scope of application. While they are applicable to all contracts, the number of special rules applicable only to consumer sales contract is in fact relatively small. Furthermore, Hungarian law provides an example of coordinated functioning of commercial and obligatory guarantees. Commercial guarantee is, like conformity, regulated uniformly in the Civil code, applicable to both consumer and non-consumer contracts. Apart from commercial guarantees, there are several obligatory guarantees in Hungarian law introduced by decrees of the government, whereby their scope of application is clear. In contrast, the legal nature and scope of application of guarantee under the Law on Obligations in Serbia became vague after the adoption of the former Law on the Protection of Consumers of 2010, which introduced commercial guarantees in consumer sale contracts. This is also one of the negative implications of the transposition of Directive 1999/44/EC into the Law on the Protection of Consumers, instead of incorporating them into the rules of general contract law. The main legislative approach adopted in the former Hungarian Civil Code has not been changed in the new Code from 2013 either: conformity and guarantee remain regulated by the general rules of contract law. Obligatory guarantees introduced by decrees of the government also remain in force. A significant novelty in the new Code is the introduction of a direct liability of the produced or consumer goods, a legislative possibility offered by Directive 1999/44/EC.
Keywords: conformity of goods, commercial guarantee, obligatory guarantee, direct liability of the producer for non-conformity